2017
DOI: 10.12659/ajcr.902535
|View full text |Cite
|
Sign up to set email alerts
|

An Eye Popping Case of Orbital Necrotizing Fasciitis Treated with Antibiotics, Surgery, and Hyperbaric Oxygen Therapy

Abstract: Patient: Female, 60Final Diagnosis: Necrotizing fasciitis of the eyeSymptoms: Eye painMedication: —Clinical Procedure: —Specialty: Infectious DiseasesObjective:Unusual clinical courseBackground:Necrotizing fasciitis (NF) of the orbit is a rare and deadly condition that requires prompt surgical and medical management to decrease morbidity and mortality.Case Report:Here we present an interesting case of an individual who developed fulminant NF of the left orbit requiring emergent surgical intervention, antibioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The primary treatment for NF is surgical debridement of the wound as soon as possible [1][2][3][4][5][6][7][8][9][10]. Some researchers have noted that NF can be effectively treated with intravenous antibiotic therapy alone (Hooi et al) [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary treatment for NF is surgical debridement of the wound as soon as possible [1][2][3][4][5][6][7][8][9][10]. Some researchers have noted that NF can be effectively treated with intravenous antibiotic therapy alone (Hooi et al) [4].…”
Section: Discussionmentioning
confidence: 99%
“…There have been studies that show hyperbaric therapy as a beneficial addition to the patient's treatment [9]. The intravenous administration of immunoglobulin G (IVIG) in the treatment of NF remains controversial [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Broad spectrum antibiotics can mask the NF and contribute to the misdiagnosis of the disease, leading to catastrophic results, since treatment including only antibiotics leads to 100% mortality [10,11] . In the present case the patient was still under broad spectrum antibiotics, but obviously it did not help him a lot.…”
Section: Discussionmentioning
confidence: 99%
“…Orbital and preseptal abscesses are SSTIs commonly caused by Staphylococcus aureus (61,62), and MRSA rates appear to be rising (63). Severe cases have been reported, including orbital and periorbital necrotizing fasciitis (64)(65)(66), necrotizing conjunctivitis with orbital invasion (12) and orbital cellulitis with bilateral involvement that progressed to blindness (14). A prospective study (2012-2015) of children and adolescents presenting with staphylococcal periorbital and orbital cellulitis in Houston found that most of the S. aureus isolates in their population were methicillin-resistant (67%) and were genetically related to the USA300 clone (78%) (67).…”
Section: Discussionmentioning
confidence: 99%